The Short-Term Impacts of COVID-19 on Households in Developing Countries : An Overview Based on a Harmonized Data Set of High-Frequency Surveys - Bundervoet, Tom; Davalos, Maria E.; Garcia, Natalia (World Bank, Washington, DC, 2021)
This paper combines new data from high-frequency surveys with data on the stringency of containment measures to examine the short-term impacts of the COVID-19 pandemic on households in developing countries. This paper is one of the first to document the impacts of COVID-19 on households across a large number of developing countries and to do so for a comparable time-period, corresponding to the peak of the pandemic-induced drop in human mobility, and the first to systematically analyze the cross- and within-country effects on employment, income, food security, and learning. Using representative data from 34 countries, accounting for a combined population of almost 1.4 billion, the findings show that in the average country, 36 percent of respondents stopped working in the immediate aftermath of the pandemic, over 64 percent of households reported decreases in income, and over 30 percent of children were unable to continue learning during school closures. Pandemic-induced loss of jobs and income translated into heightened food insecurity at the household level. The more stringent the virus containment measures were, the higher was the likelihood of loss of jobs and income. The pandemic’s effects were widespread and highly regressive, disproportionately affecting vulnerable segments of the population. Women, youth, and lower-educated workers—groups disadvantaged in the labor market before the COVID-19 shock—were significantly more likely to lose their jobs and experience decreased incomes. Self-employed and casual workers—the most vulnerable workers in developing countries—bore the brunt of the pandemic- induced income losses. Interruptions in learning were most salient for children in lower-income countries, and within countries for children in lower-income households with lower-educated parents and in rural areas. The unequal impacts of the pandemic across socioeconomic groups risk cementing inequality of opportunity and undermining social mobility and call for policies to foster an inclusive recovery and strengthen resilience to future shocks.